Tales of a long night a novel - Doblin, Alfred 1878-1957 (Fromm International Pub. Corporation, 1984)
The story of a young Englishman called Edward Allison who loses a leg during World War II and returns home a nervous as well as a physical wreck, tormented by doubt and anger, and obsessed with what seems to him the mystery of where the blame for the war really lies. He is released from a clinic in the hope that living among his family will hasten his cure, but he simply transfers his fixation with hidden guilt to the domestic front. ... In an effort to exorcise his demons, the Allisons and their friends start telling a series of stories, many of them variations on ancient myths and legends. Some of these tales serve to reveal the character of the storyteller, others as a riposte or as a comment on what has gone before. All of them are meant to advance the psychological and spiritual action. Many of the tales of Doblin's long night have an undoubted lurid power. ... We move through an expressionist phantasmagoria from a wayward bus in Los Angeles to Pluto and Proserpina, by way of Michelangelo and Salome and a mock-medieval tale about the Virgin. Edward's mother, Alice Allison (a significant name, we can be sure), spins variants of a story about a mother who waits for her son to come back from the war, now in Montmartre, now in Germany, and elaborates on the already elaborate legend of her patron saint, Theodora. In the final stages of the book the distinction between framework and fantasy starts to break down completely. Yet through the haze it is possible to discern a continuous story unfolding--fmerusault at Amazon.com.